2007
DOI: 10.1002/rcm.3164
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of analytical variation in metabonomic analysis using liquid chromatography/mass spectrometry

Abstract: Sources of analytical variation in high‐performance liquid chromatography/mass spectrometry (HPLC/MS), such as changes in retention, mass accuracy or signal intensity, have been investigated to assess their importance as a variable in the metabonomic analysis of human urine. In this study chromatographic retention and mass accuracy were found to be quite reproducible with the most significant source of analytical variation in the data sets obtained being the result of changes in detector response. Depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 18 publications
0
50
0
Order By: Relevance
“…Fourteen biologically identical serum samples (designated as QC samples) prepared from a pooled serum sample (available commercially from Sigma-Aldrich, Gillingham, UK) were analysed at intervals during a 40 h period. Data for each QC sample was acquired as analysis number 1,2,3,4,5,18,29,41,52,65,76,88,99,111 and were interdispersed with 97 other serum samples. Analysis of the samples was performed as described below.…”
Section: Reproducibility Study Using Biologically Identical Quality Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen biologically identical serum samples (designated as QC samples) prepared from a pooled serum sample (available commercially from Sigma-Aldrich, Gillingham, UK) were analysed at intervals during a 40 h period. Data for each QC sample was acquired as analysis number 1,2,3,4,5,18,29,41,52,65,76,88,99,111 and were interdispersed with 97 other serum samples. Analysis of the samples was performed as described below.…”
Section: Reproducibility Study Using Biologically Identical Quality Cmentioning
confidence: 99%
“…It has been observed for GC-MS and LC-MS data that processed data can be highly variable in respect to the number of peaks reported and reproducibility of peak areas, accurate mass and retention time [75]. Small changes in a single software parameter can greatly influence the validity and information content of results [76] and validation of software operation is required [77].…”
Section: Introductionmentioning
confidence: 98%
“…In addition, it can incorrectly remove ions with abundances that are intermittently reduced by adverse effects during ESI. This potential loss of data has been discussed recently by Wilson et al [31], who develop an algorithm using liquid chromatography mass spectrometry (LC-MS) data and propose first applying a peak intensity threshold across all mass spectra to generate one set of "real" peaks. This matrix of peak intensities will contain multiple missing values (i.e., zero intensities) since peaks present in some spectra will not be detected in others, as they are below the detection threshold.…”
mentioning
confidence: 98%
“…It is partly attributed to the MZmine software failing to utilise the entire data matrix and relying on peak detection procedures. Actually, the peak detection result strongly depends on software package and its associated parameters (unpublished data) or see reference (Sangster et al 2007). …”
Section: Analysis Of Data Processed By Mzminementioning
confidence: 99%
“…There are a range of software packages available either commercially (LECO, Waters, Shimadzu, Agilent, Applied Biosystems and SpectralWorks) or available as freeware from Open Source (including AMDIS, MZmine and XCMS) which provide deconvolution functions in their software packages. Previous research has shown that the deconvoluted results from different software packages produce distinctly different results and a range of software parameters influence chromatographic deconvolution results even for the same software package (Lu et al 2008) or see reference (Sangster et al 2007). Additionally, the deconvolution process is time-consuming and in a number of examples requires human input.…”
Section: Introductionmentioning
confidence: 97%